The Expiry of Humira® Market Exclusivity and the Entry of Adalimumab Biosimilars in Europe: An Overview of Pricing and National Policy Measures - Moorkens, Evelien; Godman, Brian; Huys, Isabelle; Hoxha, Iris; Malaj, Admir; Keuerleber, Simon; Stockinger, Silvia; Mörtenhuber, Sarah; Dimitrova, Maria; Tachkov, Konstantin; Vončina, Luka; Palčevski, Vera Vlahović; et al. (Frontiers in Pharmacology, 2021)
Background: From October 2018, adalimumab biosimilars could enter the European market. However, in some countries, such as the Netherlands, high discounts reported for the originator product may have influenced biosimilar entry. Objectives: The aim of this paper is to provide a European overview of (list) prices of originator adalimumab, before and after loss of exclusivity; to report changes in the reimbursement status of adalimumab products; and discuss relevant policy measures. Methods: Experts in European countries received a survey consisting of three parts: i) general financing/co-payment of medicines, ii) reimbursement status and prices of originator adalimumab, and availability of biosimilars, and iii) policy measures related to the use of adalimumab. Results: In May 2019, adalimumab biosimilars were available in 24 of the 30 countries surveyed. Following introduction of adalimumab biosimilars, a number of countries have made changes in relation to the reimbursement status of adalimumab products. Originator adalimumab list prices varied between countries by a factor of 2.8 before and 4.1 after loss of exclusivity. Overall, list prices of originator adalimumab decreased after loss of exclusivity, although for 13 countries list prices were unchanged. When reported, discounts/rebates on originator adalimumab after loss of exclusivity ranged from 0% to approximately 26% (Romania), 60% (Poland), 80% (Denmark, Italy, Norway), and 80% to 90% (the Netherlands). To leverage competition following entry of biosimilar adalimumab, only a few countries adopted measures specifically for adalimumab in addition to general policies regarding biosimilars. In some countries, a strategy was implemented even before loss of exclusivity (Denmark, Scotland), while others did not report specific measures. Conclusion: Even though originator adalimumab is the highest selling product in the world, few countries have implemented specific policies and practices for (biosimilar) adalimumab. Countries with biosimilars on the market seem to have competition lowering list or actual prices. Reported discounts varied widely between countries.